Age-Related Decrease of the Phosphorus Content in the Ligamentum Capitis Femoris of Monkeys - Yoshiyuki Tohno (2018)
© 2014, Springer Science+Business Media New York. To elucidate compositional changes of the ligament with aging, the authors investigated age-related changes of elements in the ligamentum capitis femoris (LCF) of monkeys with a wide range of ages by direct chemical analysis. Used rhesus and Japanese monkeys consisted of 9 males and 22 females, ranging in age from newborn to 31 years (average age = 10.4 ± 10.9 years). After incineration with nitric acid and perchloric acid, element contents were determined by inductively coupled plasma-atomic emission spectrometry. It was found that the P content decreased significantly in the LCFs of monkeys with aging, but other six element contents, Ca, S, Mg, Zn, Fe, and Na, did not change significantly with aging. Assuming that the P content indicated the active cell density and the S content indicated the protein amount, an age-related change of the mass ratio of P/S was examined in the LCFs. The mass ratio of P/S decreased significantly in the LCFs in childhood. Regarding the relationships among elements, significant direct correlations were found among the Ca, P, S, and Mg contents in the LCFs. It was suggested that the active cell density of the connective tissue cells might decrease significantly in the LCF in childhood.